Xenophobia: a hindrance factor to South Africa’s ambition of becoming a developmental state - Niyitunga, Eric Blanco (Frontiers in Human Dynamics, 2024)
The prevalence of xenophobic violence towards foreigners has hindered South Africa's ambition to become a developmental state since 2007, when the concept of a "democratic developmental state" was first endorsed during the African National Congress (ANC) conference in Polokwane. This ambition has also been thwarted by the inability of the postapartheid regime to provide adequate and sustainable services to the citizens. Xenophobia has disrupted economic growth and has contributed to poor service delivery in local municipalities, thus leading to social protests. The developmental state depends mainly on a solid balance of economic growth and human development. It also leans on the capacity of the state to establish policies that address poverty and promote the expansion of solid economic opportunities. In this endeavour, migrants increase economic growth and make it sustainable, increase productivity, and promote the labour market. They also promote the labour force and human capital, economic growth, and public finance, thus enabling the realisation of a developmental state. However, xenophobia has limited migrants' contributions to economic growth and social well-being in South Africa. It has destructive effects on South Africa's economic structure and growth, thus affecting the delivery of adequate services that would enhance its ability to achieve a developmental state. The paper recommends that there is a need for South Africa to understand that xenophobia affects economic growth and the service delivery framework. To address the prevalence of xenophobia and achieve its ambition of a developmental state, South Africa needs to hasten its responses to curb xenophobia and integrate migrants into economic opportunities. The paper adopted a qualitative research methodology and conceptual and document analysis techniques to collect data that enabled the achievement of the above assertions.